A comparison between the new Low-profile Visualized Intraluminal Support (LVIS Blue) stent and the Flow Redirection Endoluminal Device (FRED) in bench-top and cadaver studies. (22nd September 2017) - Matsuda, Yoshikazu; Chung, Joonho; Keigher, Kiffon; Lopes, Demetrius
Abstract : Object: The aim of this study is to demonstrate the differences between the new Low-profile Visualized Intraluminal Support (LVIS Blue) stenting device and the Flow Redirection Endoluminal Device (FRED) using a series of bench-top evaluations and optical coherence tomography (OCT) images in a cadaveric preparation of the basilar artery. Methods: The first part of the evaluation was bench-top microscopic documentation of metal coverage for LVIS Blue and FRED stents. OCT images of the cerebral vessels and deployed stents were acquired using OCT intravascular imaging. The stents were deployed from the left posterior cerebral artery to the basilar artery in a fresh frozen cadaver. Wall apposition and the relationship to jailed perforators were evaluated. Results: The metal coverage along the inner curves of the LVIS Blue stent was similar to that along the outer curves of the FRED stent. The LVIS Blue stent cell size was compatible for crossing with the tested microcatheters after deployment of the stent. The LVIS Blue stent showed better wall apposition and less coverage of the perforator than the FRED stent in the cadaver experiment. Conclusions: LVIS Blue has a good crossing profile for microcatheters, better wall apposition, and less perforator coverage than FRED. These are desirable features in territories with high densities of perforators such as the posterior circulation.